New and interesting Portuguese Lepidoptera records from 2023 (Insecta: Lepidoptera) - Martin F. V. Corley; José L. Fabião; Paulo Lemos; João Nunes; Jorge Rosete (SHILAP)
Twenty species are added to the Portuguese Lepidoptera fauna, of which two are new for the Iberian Peninsula, and four species deleted, mainly as a result of fieldwork undertaken by the authors and others in 2023. In addition, second to fourth records for the country, new province records and new host-plant data for a number of species are included. A summary of recent papers affecting the Portuguese fauna is presented.